Five millimeters Lateral Trocar Incarcerated Hernia Following Laparoscopic Cholecystectomy: A Case Report - Girgin, Mustafa; Kanat, Burhan Hakan; Cetinkaya, Ziya; Ayten, Refik; Bozdag, Ahmet (Aves, 2013)
The prediction of hernia developing from 10 and 12-mm port site is an important foresight among surgeons. To prevent this, surgeons sutures the fascia of ports larger than 10 mm, but they do not sutures the fascia of 5 mm port, because they do not expect development of hernia from here. A case of an operated woman because of incarcerated hernia from 5 mm trocar site is reported. Mayo herniorrhaphy was performed to a women who had incarcerated hernia at 5 mm lateral trocar site. Five mm trocar site hernia is rare but must be considered and if possible, must be primary closed during laparoscopic surgery.
Laparoskopi sonrasi{dotless} beş milimetre lateral trokar yerinde İnkarsere herni: Olgu sunumu
Keywords: Laparoscopy; trocar site herniation; incarcerated hernia